Felicidade e políticas públicas: o sentir, o pensar e o agir - Ribeiro Júnior, Wilson de Souza (2013)
Happiness has been always discussed in philosophy throughout the history of humankind, influencing the way we live and organize the most different societies. In recent years, the academic study on the subject has grown exponentially in the most diverse areas of knowledge. Such that the main objective of this research is to raise, characterize and analyze the specific production on happiness and public policy. For this purpose, we make a research over literature on happiness/subjective well-being and public policy, from articles indexed in databases of national and international data and other complementary methods, allowing to identify the major works and researchers. Then such literature is analyzed from the perspective of systems thinking and the selected theoretical framework in order to generate a holistic view of the concept of happiness: Seeing, Knowing and Doing. The result is an updated and critical mapping of the study of this field by characterizing the existing academic literature on the epistemological, ontological and methodological dimensions. It was found that the subject happiness in the public policies is accompanying the recent exponential growth of hapiness studies, representing, nevertheless, a small portion of this universe. Predominate the anglo-saxon authors and research centers and the economy as the main area of knowledge. The interdisciplinary approach is the hallmark of the analyzed works, aligning to them, in order of impact, economics, psychology, philosophy and sociology. Experiments are mostly still rare and inconsistent systematized. Nevertheless, it is considered that literature and the practical experiences have a fast developmet with enough elements to a more ethical and comprehensive overview of development and evaluation of public policies.